2016
DOI: 10.1111/avsc.12271
|View full text |Cite
|
Sign up to set email alerts
|

Formalized classification of European fen vegetation at the alliance level

Abstract: Aims Phytosociological classification of fen vegetation (Scheuchzerio palustris‐Caricetea fuscae class) differs among European countries. Here we propose a unified vegetation classification of European fens at the alliance level, provide unequivocal assignment rules for individual vegetation plots, identify diagnostic species of fen alliances, and map their distribution. Location Europe, western Siberia and SE Greenland. Methods 29 049 vegetation‐plot records of fens were selected from databases using a list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 72 publications
2
107
1
2
Order By: Relevance
“…The second dataset consists of 1,510 vegetation plots (Figure ) sampled in areas from 1 to 100 m 2 assigned to mountain base‐rich fens (hereafter, rich fens) in a pan‐European classification (Jiménez‐Alfaro et al., ). This study found this range of plot sizes appropriate for describing the alliance Caricion davallianae (Peterka et al., ), which is mainly associated with base‐rich and waterlogged soils in cool areas with high precipitation (Essl, Dullinger, Moser, Rabitsch, & Kleinbauer, ; Jiménez‐Alfaro et al., ). This vegetation characterizes the European protected habitat “7230 Alkaline fens” and the EUNIS type “D4.1—Rich fens, including eutrophic tall‐herb fens and calcareous flushes and soaks” (Šefferová Stanová, Seffer, & Janák, ).…”
Section: Methodsmentioning
confidence: 83%
“…The second dataset consists of 1,510 vegetation plots (Figure ) sampled in areas from 1 to 100 m 2 assigned to mountain base‐rich fens (hereafter, rich fens) in a pan‐European classification (Jiménez‐Alfaro et al., ). This study found this range of plot sizes appropriate for describing the alliance Caricion davallianae (Peterka et al., ), which is mainly associated with base‐rich and waterlogged soils in cool areas with high precipitation (Essl, Dullinger, Moser, Rabitsch, & Kleinbauer, ; Jiménez‐Alfaro et al., ). This vegetation characterizes the European protected habitat “7230 Alkaline fens” and the EUNIS type “D4.1—Rich fens, including eutrophic tall‐herb fens and calcareous flushes and soaks” (Šefferová Stanová, Seffer, & Janák, ).…”
Section: Methodsmentioning
confidence: 83%
“…This work is another contribution towards the construction of the formalized classification system of European vegetation, complementing the series of recent studies focusing on the diversity of selected vegetation types across the whole of Europe (Douda et al, ; Peterka et al, ; Willner et al, ; Marcenò et al, ). At the same time, we hope it can also become a step towards the construction of a supra‐continental classification of wetlands.…”
Section: Discussionmentioning
confidence: 74%
“…The threshold values of percentage cover in the formulas were assigned arbitrarily following our personal experience and consistently with similar classifications developed in the past (Chytrý, ; Landucci, Tichý, et al, ; Peterka et al, ). Assignment rules based on the overall physiognomy of the vegetation stands ▫︎If the total cover of the group ‘shrubs and trees’ (group N.C) is >25% or that of ‘other herbaceous plants and dwarf shrubs’ (N.B) is >50%, the plot does not belong to marsh vegetation of the Phragmito‐Magnocaricetea class, irrespective of the cover value of marsh species (included in the group N.A). ▫︎If the previous point is not true and the total cover of ‘competitive marsh forbs’ (N.A.3) is >25%, the plot is assigned to an association defined by species belonging to this group, irrespective of the cover value of other marsh species (included in N.A.1, N.A.2). ▫︎If the previous point is not true and the total cover of ‘emergent reedlike plants and bulrushes’ (N.A.2.1) and ‘marsh sedges’ (N.A.2.2) is >25%, the plot is assigned to an association defined by species belonging to these groups irrespective of the cover value of other marsh forbs (included in N.A.1). ▫︎If the previous point is not true and the total cover of ‘amphibian plant species’ (N.A.1.1) and ‘less competitive marsh forbs’ (N.A.1.2) is >25%, the plot is assigned to an association defined by species belonging to these groups. Assignment rules based on species dominance (valid if at least one of the assignment rules according to the overall physiognomy is met) ▫︎If no species in a marsh vegetation plot has a cover ≥25%, the plot is assigned to the association characterized by the species that dominates the vegetation in the plot (the species with the highest cover value in the plot). ▫︎If the cover of a particular ‘marsh plant species’ (any species included in N.A) is >25%, the plot is assigned to the association characterized by that species. ▫︎If two or more species have identical cover values, the assignment of the plot is based on the priority degrees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, this group of species is represented especially by Primula farinosa (Hájek et al., ; Theodoridis et al., ) and Saxifraga hirculus (Dítě et al., ). The effects of relictualism and the type of nature limitation might multiply in Saxifraga hirculus , the species with the greatest effect of latent variables that shows affinity to both the relict sites (Hájek et al., ; Dítě et al., ) and the N‐ instead of P‐limited sites (the Saxifrago‐Tomentypnion alliance, Peterka et al., ).…”
Section: Discussionmentioning
confidence: 99%